Iatrogenic Gallbladder Perforation Treated by Laparoscopic Cholecystectomy - S Graham; S Hermann; WT Depew; RF Pace (Canadian Journal of Gastroenterology)
A case of gallbladder perforation with bile peritonitis resulting from a percutaneous needle biopsy of the liver is presented. Using laparoscopic cholecystectomy as the surgical management, the patient made a rapid and smooth recovery.